2015
DOI: 10.1002/ab.21621
|View full text |Cite
|
Sign up to set email alerts
|

“It was only harmless banter!” The development and preliminary validation of the moral disengagement in sexual harassment scale

Abstract: Sexual harassment represents aggressive behavior that is often enacted instrumentally, in response to a threatened sense of masculinity and male identity. To date, however, theoretical attention to the social cognitive processes that regulate workplace harassment is scant. This article presents the development and preliminary validation of the Moral Disengagement in Sexual Harassment Scale

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 164 publications
1
41
1
Order By: Relevance
“…Hostile sexism thus coheres with initial definitions of prejudice as antipathy (e.g., Allport, 1954), and can serve to justify men's exploitation of women as sexual objects. Indeed men are typically higher in hostile sexism than women (Glick et al, 2000), and hostile sexism is associated with a greater tolerance of sexual harassment, increased moral disengagement from sexual harassment, and even a higher proclivity to commit sexual assault (Abrams, Viki, Masser, & Bohner, 2003;Masser, Viki, & Power, 2006;Page, Pina, & Giner-Sorolla, 2016;Russell & Trigg, 2004). Glick and Fiske (1996) further introduced another form of sexism termed benevolent sexism, which involves an apparently positive, yet patronizing, stance toward women (i.e., that women need to be cherished and protected).…”
Section: Men and Women Differ In Ideologies Related To Sexual Misconductmentioning
confidence: 99%
“…Hostile sexism thus coheres with initial definitions of prejudice as antipathy (e.g., Allport, 1954), and can serve to justify men's exploitation of women as sexual objects. Indeed men are typically higher in hostile sexism than women (Glick et al, 2000), and hostile sexism is associated with a greater tolerance of sexual harassment, increased moral disengagement from sexual harassment, and even a higher proclivity to commit sexual assault (Abrams, Viki, Masser, & Bohner, 2003;Masser, Viki, & Power, 2006;Page, Pina, & Giner-Sorolla, 2016;Russell & Trigg, 2004). Glick and Fiske (1996) further introduced another form of sexism termed benevolent sexism, which involves an apparently positive, yet patronizing, stance toward women (i.e., that women need to be cherished and protected).…”
Section: Men and Women Differ In Ideologies Related To Sexual Misconductmentioning
confidence: 99%
“…"anonymous and toxic gamer" collective identity (Tang and Fox, 2016). Some researchers have gone so far as to predict that the normalization of these behaviors within gamer culture could eventually shift and/or sustain cultural norms toward eventually seeing harassment in-games as harmless and acceptable (Ross and Weaver, 2012;Page et al, 2016).…”
mentioning
confidence: 99%
“…Research has identified multiple social and cognitive factors that predict increased involvement in relational aggression (e.g., Boxer, Goldstein, Musher-Eizenman, Dubow, & Heretick, 2005;Martinelli, Ackermann, Bernhard, Freitag, & Schwenck, 2018), and to a lesser extent research has identified similar factors associated with sexual harassment (e.g., Page, Pina, & Giner-Sorolla, 2016). This being said, both the potential role of the peer context and the way in which the individual adolescent is orientated toward her/his peer relationships have been less extensively explored as predictors of these detrimental behaviors.…”
mentioning
confidence: 99%